Demography and democracy - Haghighat, Elhum. (Cambridge)
xvii, 261 sayfa
Keywords: “Demographically, the Middle East and North Africa (MENA) region has one of the highest population growth rates in the world. The demographic shifts have profoundly affected economic, political, and social institutions. Furthermore, the recent period of unprecedented political turbulence has complicated the picture. In 2010, MENA political uprisings and resistance movements began in Tunisia and spread to Egypt, Libya, and Yemen. Civil uprisings erupted in Bahrain and Syria; in Bahrain it was short-lived while in Syria it has evolved into a continuous and violent crisis. More uprisings emerged in different countries of the MENA such as Algeria, Iraq, Jordan, Kuwait, Morocco, Oman, Saudi Arabia, and Lebanon, and clashes arose along the borders of the Israeli and Palestinian territories. Granted, uprisings are not new phenomena in the MENA region, but the timing, the domino effect, and the level of intensity of the current shifts in culture, politics, and economics deserve critical evaluation.” --